Towards Mitigating Teenagers' Distracted Driving Behaviors: Comparison of Real-Time and Post-Drive Feedback in a Simulator Study. (September 2016) - Merrikhpour, Maryam; Donmez, Birsen
Distraction contributes significantly to teens' crash risks. Previous studies show that feedback can help mitigate distraction among young and adult drivers; however, the type of feedback that is effective for teenagers remains unexamined. This paper investigates whether real-time and post-drive feedback can mitigate teens' driver distraction and reports preliminary findings from an ongoing simulator study. Data reported was collected in a between-subjects experiment with three conditions: real-time (n= 8), post-drive (n= 8), and no feedback (n= 9). Real-time feedback was provided as auditory warnings when teens had long offroad glances (>2 sec). Post-drive feedback was an end-of-trip report on teens' off-road glances and driving performance provided on an in-vehicle display. Compared to no feedback, real-time feedback resulted in significantly smaller number of long off-road glances (>2 sec), smaller average duration of off-road glances, and smaller standard deviation of lane position. The effects observed for post-drive feedback were relatively minor.